2018
DOI: 10.3389/fvets.2018.00294
|View full text |Cite
|
Sign up to set email alerts
|

A Survey-Based Investigation of Human Factors Associated With Transport Related Injuries in Horses

Abstract: Injuries resulting from road transport are common in horses and are a potential welfare concern, as well as, a source of economic loss. An online cross sectional survey was used to determine the prevalence of road transport related injuries to horses in New Zealand and the association of human factors including demographics, industry background, training and the horse handling experience of the respondents with transport related injury. The survey generated 1133 valid responses that were analyzed using descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…The findings of the current study carried out in the UK agree with those of comparable surveys conducted in Australia [6] and New Zealand [7], that those who transport horses for competitive and/or professional purposes were more likely to have experienced a transport-related incident than those transporting for leisure and recreation. This is in part likely to be a consequence of the increased frequency of travel, as well as the greater number of horses managed by those in the professional sector [7]. In Australia, in a survey of horse injury during non-commercial transport, 24.7% of participants reported transport-related injuries to their horses [6].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The findings of the current study carried out in the UK agree with those of comparable surveys conducted in Australia [6] and New Zealand [7], that those who transport horses for competitive and/or professional purposes were more likely to have experienced a transport-related incident than those transporting for leisure and recreation. This is in part likely to be a consequence of the increased frequency of travel, as well as the greater number of horses managed by those in the professional sector [7]. In Australia, in a survey of horse injury during non-commercial transport, 24.7% of participants reported transport-related injuries to their horses [6].…”
Section: Discussionsupporting
confidence: 87%
“…The scale of the problem and the prevalence of injuries sustained during non-commercial transportation for sport, leisure and related purposes has yet to be determined. Recent surveys conducted in Australia [6] and New Zealand [7] indicate that transport-related incidents in the equine sporting and leisure sectors are not uncommon, with the potential scale of the problem dependent upon transportation frequency [7]. In the United Kingdom (UK), an online survey of horse owners found that approximately 60% of respondents regularly transported their horse to attend events and activities [8] and a cross-sectional UK study found that, out of a sample of 797 survey respondents, 22.5% had transported their animals within the previous week (54.7% in a trailer, 41.3% in a horsebox, and 3.9% used both) [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transportation has been identified as a stressor for horses, and has been associated with several adverse outcomes including injury, respiratory and gastrointestinal disease [1][2][3][4][5][6]. We have recently shown that 12 hours' transportation is associated with ulceration of the gastric squamous mucosa in fasted horses, associated with increased pH of gastric content, and possibly with decreased gastrointestinal motility in horses fed 1 h and 6 h prior to transportation [7].…”
Section: Introductionmentioning
confidence: 99%